Characterization of ionic transport through BaCe0.2 Zr0.7Y0.1O3−δ membranes in galvanic and electrolytic operation. (10th August 2015) - Babiniec, Sean M.; Ricote, Sandrine; Sullivan, Neal P.
Abstract: Proton-conducting ceramic electrochemical devices were fabricated consisting of a 25-μm-thick BaCe0.2 Zr0.7 Y0.1 O3− δ (BCZY27) electrolyte membrane supported on a 1-mm-thick Ni/BCZY27 fuel electrode, and an air electrode consisting of a 40-μm-thick porous BCZY27 backbone infiltrated with La2 NiO4+ δ catalyst. Hydrogen flux was measured as a function of gas environment at the air electrode and as a function of applied cell potential and current at 700 °C. The hydrogen transference number decreased significantly, reaching levels as low as 0.05 when hydrogen is transported against the concentration gradient, even with reducing gas environments on both sides of the membrane. Additionally, the hydrogen transference number decreased with increasing applied potential and current. The decrease in hydrogen transport efficiency must be compensated by an ionic or electronic flux. These results show that charge transfer in these materials can be dominated by electronic defects in high-current electrolytic regimes, without the need for ionic co-transport. Highlights: We detail fabrication of thin-membrane devices using the BCZY27 protonic-ceramic. We examine ion flux by monitoring gas composition as a function of polarization. Hydrogen flux shows a large deviation from faradaic flux in electrolytic operation. Electrochemical reduction of cerium is proposed as mechanism for n-type defects. Results show unfavorable performance of BCZY27 ceramics as electrolysis membranes.